Comparison of the Effectiveness of DNA Extraction Methods in Body Identification - Boichenko, Yevheniia; Boika, Olena (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2025)
This paper compares DNA extraction methods used in forensic investigations for individual identification. It analyses the advantages and disadvantages of the primary techniques em-ployed in routine forensic examinations at the Zaporizhzhia Scientific and Research Forensic Center of the Ministry of Internal Affairs of Ukraine. Emphasis is placed on the criteria for selecting a specific method, depending on the circumstances and the available biological material.
Keywords: identification of bodies; DNA methods; forensic investigation